Emotion regulation and virtual nature: cognitive reappraisal as an individual-level moderator for impacts on subjective vitality - Theodorou, Annalisa; Spano, Giuseppina; Bratman, Gregory N.; Monneron, Kevin; Sanesi, Giovanni; Carrus, Giuseppe; Imperatori, Claudio; Panno, Angelo (Scientific reports, 2023)
People who make habitual use of an emotion regulation strategy such as cognitive reappraisal may be more sensitive to the emotion cues coming from a surrounding natural environment and, thus, get more benefits from virtual nature exposure such as enhanced subjective vitality. However, no previous study investigated the moderating role of cognitive reappraisal in the relationship between exposure to different types of natural environments (a national park, a lacustrine environment, and an arctic environment vs. an urban environment) and subjective vitality. We designed a between-subject design (four conditions, one per type of environment) with a sample of 187 university students (M age = 21.17, SD = 2.55). Participants were exposed to four 360° panoramic photos of the environment for one minute each with a virtual reality head-mounted display. The results of a multicategorical moderation analysis attested that there were two significant interactions, respectively between lacustrine and arctic environments and cognitive reappraisal. More specifically, for participants with low levels of habitual use of cognitive reappraisal, the effects of virtual nature (vs. urban) exposure on subjective vitality were not significant, while for participants with high levels, the effects were significant and positive. Findings show how the potential of virtual nature may be boosted with training aimed at increasing the general use of cognitive reappraisal, supports enhancing the applications of virtual nature, and demonstrates the need to take individual differences into account when determining the benefits of these applications.